The implementation of guidance and counseling services in overcoming the cheating habit of high school students - Pranowo, Taufik Agung; Santoso, Ardhian Rohmad (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
This study aims to determine the implementation of guidance and counseling services conducted by the counselor at SMA N 1 Pajangan in overcoming student cheating problems. Research conducted in this study uses qualitative methods with a descriptive approach. There are two data used in this study, namely primary data and secondary data. Data collection techniques are used observation and interviews. The data analysis used was data reduction, data creation, and conclusions. The result of this study is counselors provide guidance and counseling services to overcome cheating behavior by collaborating with subject teachers. The services cover student experiences with motivation. The conclusion is the role of guidance and counseling teachers on students’ cheating habits is very good. There is a cooperation between counselors and subject teachers to be able to overcome this problem.